Pengujian Alat Bukti Dalam Penetapan Tersangka di Praperadilan : Studi Kasus Putusan Praperadilan di Pengadilan Negeri Jakarta Selatan - Danang Dermawan; Syafruddin Kalo; Madiasa Ablisar; Mahmud Mulyadi (Universitas Sumatera Utara, 2019)
Abstract. To protect human rights, especially against suspects or defendants, the KUHAP regulates a pretrial institution. Arrangements regarding pretrial are limitative and not all forced efforts can be submitted to pretrial requests. However, through the Decision of the Constitutional Court Number 21 / PUU-XII / 2014, adding the testing of the determination of suspects, searches, and seizure into the pretrial authority. However, the weak rules that only consist of 7 articles, namely Article 77 of the Criminal Procedure Code up to article 83 of the Criminal Procedure Code so that the testing of the validity of a suspect's determination is focused on the process of collecting evidence. Pre-trial verdict No. 97 / Pid.Prap / 2017 / PN.Jkt.Sel, No 36 / Pid.Prap / 2015 / PN.Jkt.Sel, No. 32 / Pid.Prap / 2015 / PN.Jkt.Sel, and No. 127 / Pid.Prap / 2016 / PN.Jkt.Sel became the focus of attention in this study. The formulation of the problem in this thesis research is how to find evidence in the determination of suspects by KPK investigators on the four pretrial decisions, how to test evidence in the determination of suspects in pretrial trials by judges who decide on the four pre-trial decisions, and how the KPK's legal remedies cancellation of the determination of suspects in the four pre-trial decisions. The results showed in finding evidence on the determination of suspects in the pre-trial verdict which by KPK investigators is basically carried out by KPK according to KPK SOP Number 01/23/2008 Year 2008 and updated 2015 KPK SOP by finding at least two evidences so that the Investigation Order has stated name of the suspect. Keywords: pretrial, determination of suspects, testing of evidence, legal efforts.